Peter Pan in return to Never Land - Budd, Robin; Cook, Donovan; Mathews, Temple; Barrie, J. M. (James Matthew), 1860-1937.; Walt Disney Pictures; Walt Disney Home Video (Firm); Buena Vista Home Entertainment (Firm) (Burbank, Calif. : Disney DVD : Distributed by Buena Vista Home Entertainment, 2002)
In London during World War II, Wendy comforts her children with stories about her youthful adventures with Peter Pan in the fantastic world of Neverland. Young Danny loves the stories and believes that they're real, but his older sister, Jane, isn't so certain. Jane soon discovers her mother is indeed telling the truth when she's kidnapped by the evil Captain Hook, who is still trying to capture his nemesis, Peter Pan. Peter comes to the aid of young Jane, but as they do battle with Hook, he realizes it will take some work before Jane will fit in with the Lost Boys.
Title fom disc label.
For special features, see interactive menus.
Based on the characters from the book "Peter Pan" by James M. Barrie.
Score composed & conducted by Joel McNeely.
Voices: Harriet Owen, Blayne Weaver, Corey Burton, Jeff Bennett, Kath Soucie, Andrew McDonough, Roger Rees, Spencer Breslin, Bradley Pierce.
Rated G by the MPAA.
Keywords: Peter Pan (Fictitious character) -- Juvenile drama; Feature films; Films for the hearing impaired; Animated films; Children's films